Unilateral giant renal angiomyolipoma and pulmonary lymphangioleiomyomatosis - Fernando Peixoto Ferraz de Campos; Cristiane Rúbia Ferreira; Angélica Braz Simões; Paulo Sergio Martins de Alcântara; Brenda Margatho Ramos Martines; Adriano Ferreira da Silva; Deborah Azzi-Nogueira; Luiz Roberto Giorgetti de Britto; Luiz Gustavo Dufner-Almeida; Luciana Amaral Haddad (University of São Paulo, 2013)
Angiomyolipomas (AMLs) are mesenchymal neoplasms, named so because of the complex tissue composition represented by variable proportions of mature adipose tissue, smooth muscle cells, and dysmorphic blood vessels. Although AMLs may rise in different sites of the body, they are mostly observed in the kidney and liver. In the case of renal AMLs, they are described in two types: isolated AMLs and AMLs associated with tuberous sclerosis (TS). While most cases of AMLs are found incidentally during imaging examinations and are asymptomatic, others may reach huge proportions causing symptoms. Pulmonary lymphangioleiomyomatosis (LAM) is a rare benign disease characterized by cystic changes in the pulmonary parenchyma and smooth muscle proliferation, leading to a mixed picture of interstitial and obstructive disease. AML and LAM constitute major features of tuberous sclerosis complex (TSC), a multisystem autosomal dominant tumor-suppressor gene complex diagnosis. The authors report the case of a young female patient who presented a huge abdominal tumor, which at computed tomography (CT) show a fat predominance. The tumor displaced the right kidney and remaining abdominal viscera to the left. Chest CT also disclosed pulmonary lesions compatible with lymphangioleiomyomatosis. Because of sudden abdominal pain accompanied by a fall in the hemoglobin level, the patient underwent an urgent laparotomy. The excised tumor was shown to be a giant renal AML with signs of bleeding in its interior. The authors call attention to the diagnosis of AML and the huge proportions that the tumor can reach, as well as for ruling out the TSC diagnosis, once it may impose genetic counseling implications.